High-Temperature MBE Manipulator for SiC Substrate Preparation and GaN Growth - Lapila, Eero (My University, 2023)
Chemo-mechanically polished silicon carbide (SiC) substrates, intended for gallium nitride (GaN) growth, often exhibit poor surface quality. Sublimation etching presents a potential solution to enhance the SiC surface quality with the absence of any additive etching gases. Sublimation etching of SiC requires extremely high temperatures, approximately 1500 °C. This thesis focuses on the design and testing of a high-temperature manipulator created for the sublimation etching of 4" SiC substrates, especially for use in molecular beam epitaxy (MBE) processes. The manipulator design phase involved material research to select a material for the heating element. Two materials, tungsten and graphite were chosen, with the latter being replaced with carbon fiber-reinforced carbon due to availability issues. Other materials of the manipulator remained consistent with previous designs of DCA Instruments models. The manipulator's geometry mainly follows previous models, with the addition of a novel heater design, enhanced heat shielding and an improved cooling system. Comsol Multiphysics software was employed to perform simulations with the new manipulator design. This aimed to simulate temperature distribution across the substrate and manipulator, with different values of heating power. Subsequently, tests were performed using the newly designed manipulator. The tungsten heater exhibited bending and deformation already at temperatures under 1000 °C. However, conversely the carbon fiber-reinforced carbon heater achieved a temperature of 1600 °C on the SiC substrate. After heating to 1600 °C, AFM scans of SiC substrate showed significant surface deformation. This indicates the manipulator is capable of performing sublimation etching of SiC since the etching and surface preparation usually occur below the temperature at which the substrate starts to deform. GaN film growth on SiC substrates plays a crucial role in current and future high-power applications. The high-temperature manipulator facilitates SiC substrate preparation through sublimation etching and eliminates the need for additional etching gases. Consequently, substrate preparation and thin film growth can be executed using a single manipulator within a single chamber, resulting in resource savings.
Keywords: MBE, SiC, GaN, Sublimation Etching